Prevalence and associates of obesity and overweight among school-age children in a rural community of Thailand - Teechaya Nonboonyawat; Wuttipat Pusanasuwannasri; Nattanon Chanrat; Natta Wongthanavimok; Danutanut Tubngern; Piengkwan Panutrakul; Mathirut Mungthin; Thirapa Nivesvivat; Panadda Hatthachote; Ram Rangsin; Phunlerd Piyaraj (Korean Pediatric Society, 2019)
Purpose Information about overweight and obesity among students in rural areas of Thailand is limited. Therefore, we aimed to determine overweight and obesity prevalences and associated factors among school-aged children in a rural community of Thailand. Methods We selected 9 public schools through cluster sampling in 2 provinces located in central Thailand in 2016. Anthropometric measurements were measured using standard techniques, classified as overweight (>1 standard deviation [SD]) and obese (>2 SD) with respect to their age and sex using 2007 World Health Organization reference charts. Standardized questionnaires on risk factors were sent to parents to be completed together with their child. Results Among 1,749 students, 8.98% had overweight and 7.26% had obesity. Mean age (range) was 11.5 years (5-18 years). Independent factors associated with overweight and obesity included primary school student (reference as secondary school) (adjusted odds ratio [aOR], 2.25; 95% confidence interval [CI], 1.24-4.08; P=0.07), mother's body mass index (aOR, 1.07; 95% CI, 1.02-1.12; P=0.001), self-employed father (aOR, 1.99; 95% CI, 1.12-3.55; P=0.018), number of siblings (aOR, 0.61; 95% CI, 0.47-0.81; P=0.001), having sibling(s) with obesity (aOR, 1.82; 95% CI, 1.20-2.77; P=0.005), more than one (aOR, 7.16; 95% CI, 2.40-21.32; P<0.001), consuming 2-3 ladles of rice/meal (aOR, 2.14; 95% CI, 1.38-3.32; P=0.001), consuming >3 ladles of rice/meal (aOR, 2.69; 95% CI, 1.11-6.46; P= 0.27), watching <2 hours of television/day (aOR, 2.18; 95% CI, 1.19-4.01; P=0.012), and watching >2 hours of television/day (aOR, 2.60; 95% CI, 1.36-4.96; P=0.004). Conclusion Many sociodemographic, dietary, and behavioral factors were related to overweight and obesity among school-aged children not only in urban but also rural communities of Thailand.